The Relationship between Sustainability and Resilience in Supply Chains: An Empirical Study on the Egyptian Manufacturing Firms - El Damaty, Ali Mahmoud; Ragheb, Mohamed A.; Abdrabou, Mohamed H.; Khalaf, Magdy A. (The Arab Journal of Administration, 2025)
In the face of increasing environmental concerns, market volatility, and global disruptions, the imperative for sustainable and resilient supply chains has never been more pronounced. This study aims to explore the relationship between the implementation of sustainable supply chain management (SSCM) practices and the achieved level of supply chain resilience (SCR) within the context of the Egyptian manufacturing firms. Employing a quantitative approach that includes analysis of survey data from 396 Egyptian manufacturing firms, this study reveals that SSCM practices are significantly correlated with enhanced SCR, suggesting that sustainability-oriented strategies are crucial for building resilient supply chains. This research contributes to the literature in several ways. First, it adds to the existing knowledge about the SSCM-SCR relationship in general, and within the developing countries context, in specific. Second, it adopts a new operationalization approach for the SSCM practices by merging social and economic practices within a single factor and separating supplier management practices from internal environmental management practices. Third, it provides empirical evidence for supporting the role of implementing SSCM practices in enhancing SCR within the developing countries context. Thus, this research offers practical insights for managers, aiming to fortify their supply chains against disruptions while concurrently advancing sustainability goals. It suggests that Egyptian manufacturing firms can significantly benefit from integrating environmental, economic, and social sustainability practices into their supply chain operations. This integration provides a competitive edge by increasing the resilience of supply chains, thus ensuring business continuity and reducing vulnerability to external shocks.